The Individual Program of Psychological Support for Teaching Staff from Youth Educational Centres - Justyna Maria Siemionow (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: Teachers who work in the Youth Educational Centres often come across difficult and demanding situations, which makes them adapt to changing circumstances in internal and external reality, i.e. social and cultural environment. The staff have to become adjusted to these challenges and build their self-efficiency at the same time. It is closely related to the process of improving their convictions that they have appropriate skills in coping with daily difficulties. The teachers also perceive those as challenges not as threats. In order to prevent the teachers' mental overload while upbringing youths with learning disabilities, emotional and behavioral disorders, the long-term, systematic programs are essential. One of the examples may be the program under discussion. Research Aim: Description of the individual supporting program for Youth Educational Centres staff and presentation of the preliminary program with six participants from different institutions. Evidence-based Facts: Although the results of research conducted with the professional burnout phenomenon are known and described widely, there is relatively little information about the specific prevention tasks, especially in the group of teachers working with troubled youths. Summary: The teaching staff from Youth Educational Centres have participated in various forms of professional development, e.g. workshops, courses, lectures. They make teachers more effective in their efforts. At present, there is a strong need to take care of the employees' mental health in these institutions. This problem has been particularly visible during the COVID-19 pandemic and its consequences and now it is time to introduce individual standard support procedures in educational work in Youth Educational Centres.